Fossilized diatoms as indirect indicators of the origin of carbon stored in intertidal flats - El-Hacen, El-Hacen M.; Mens, Ties; Bouma, Tjeerd J.; Piersma, Theunis; Leroy, Suzanne A.G.; Olff, Han; Sangiorgi, Francesca (Frontiers in Marine Science, 2022)
Coastal systems store enormous carbon quantities in their sediment, which originates from various autochthonous and allochthonous sources. Carbon fluxes in coastal ecosystems have a strong effect on the recipient food-webs and carbon emission offsets. Yet, the relative importance of autochthonous vs. allochthonous C inputs to coastal carbon budget is still challenging to identify. Here, we combine diatoms preserved in the sediment with geochemical analyses to identify the sources of carbon stored in Africa’s largest intertidal seagrass beds at Banc d’Arguin, Mauritania. The area lies between an active ocean upwelling and the ‘Sahara-dust hotspot’ systems. The extensive seagrass beds of the area are thus expected to receive C from these neighboring systems in addition to producing C in-situ. Three sediment cores (50 cm) were collected at three intertidal sites with different hydrodynamic regimes, and analyzed for diatom composition, total organic carbon (TOC), total nitrogen (TN), total phosphorus (TP), and carbon isotopic signatures (δ13C). Diatom taxa are grouped into three guilds: (1) benthic (epiphyte, epipelon, and epipsammon), (2) planktonic, and (3) freshwater. Benthic diatoms are considered to be autochthonous, while typical oceanic and freshwater diatoms are considered to be allochthonous. Benthic diatoms are the most diverse and abundant group, while allochthonous freshwater (i.e., dust imported) and typical upwelling (i.e., tidal imported) taxa ranked last in both abundance and species’ richness. Structure equation modelling shows that variation in the stored carbon is best explained by the total abundance of diatoms and guild composition. We conclude that the C stored in the intertidal seagrass beds of Banc d’Arguin is predominantly autochthonous. Our method provides an effective way to identify historical carbon sources in coastal systems.